Can mediated communication moderate the relationship between being in isolation and quarantine for COVID-19 and loneliness? - Kashian, Nicole (Cyberpsychology: Journal of Psychosocial Research on Cyberspace, 2022)
An online survey examined if and how aspects of mediated communication were associated with less loneliness while in isolation and quarantine for COVID-19. A national sample of 490 US participants who were either in isolation, quarantine, or in neither, answered questions regarding their use of mediated communication, the people with whom they communicated, perceived social presence, active and passive social media use, and perceived loneliness. SPSS software was used to run a multivariate regression model to test these potential moderators using a Hochberg (1988) correction for familywise error. For people in isolation and quarantine, relative to neither, the more they used mediated communication with a high degree of social presence, such as voice calls and video calls, the more loneliness they reported. The data also indicate that for those who are not in quarantine or isolation in a pandemic, using mediated communication with a high degree of social presence is related to less loneliness.